A randomized controlled clinical trial of the effect of supportive counseling on mental health in Iranian mothers of premature infants - Leila Seiiedi-Biarag; Mojgan Mirghafourvand; Khalil Esmaeilpour; Shirin Hasanpour (BMC Pregnancy and Childbirth, 2021)
Abstract Background Premature birth can affect maternal mental health. Considering that the mental health disorder in mothers may play a vital role in the growth and development of their children, therefore, this study was conducted to determine the effect of supportive counseling on mental health (primary outcome), mother-child bonding and infant anthropometric indices (secondary outcomes) in mothers of premature infants. Methods This randomized controlled clinical trial was carried out on 66 mothers with hospitalized neonates in the NICU of Alzahra hospital in Tabriz- Iran. Participants were randomly allocated into two groups of intervention (n = 34) and control (n = 32) through a block randomization method. The intervention group received 6 sessions of supportive counseling (45–60 minutes each session) by the researcher, and the control group received routine care. Questionnaires of Goldberg General Health and the postpartum bonding were completed before the intervention (first 72 hours postpartum) and 8 weeks postpartum. Also, the anthropometric index of newborns were measured at the same time. Results There was no statistically significant difference between the two groups in terms of socio-demographic characteristics. After the intervention, based on ANCOVA with adjusting the baseline score, mean score of mental health (AMD: -9.8; 95% Confident Interval (95% CI): -12.5 to -7.1; P < 0.001) and postpartum bonding (AMD: -10.0; 95% CI: -0.6 to 13.9; P < 0.001) in the counseling group was significantly lower than those of the control group; however, in terms of weight (P = 0.536), height (P = 0.429) and head circumference (P = 0.129), there was no significant difference between the two groups. Conclusions Supportive counseling may improve mental health and postpartum bonding in mothers of premature infants. Thus, it may be recommendable for health care providers to offer it to mothers. Trial registration Iranian Registry of Clinical Trials (IRCT): IRCT20120718010324N45 . Date of registration: October 29, 2018.